Implementation of Core Learning Model to Improve Mathematical Literacy Students - Nasrulloh, M Farid; Umardiyah, Fitri; Hidayatulloh, Faisol; Maksum, Mohammad Jafar Sodiq; Putri , Sania Eliza (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
This research was conducted with the aim of knowing differences in the mathematical literacy abilities of class VIII students of MTs Salafiyah Syafiiyah Bandung before and after applying the CORE (Connecting, Organizing, Reflecting, Extending) learning model. The research method used is a pre-experimental design with a one-group pretest-posttest design and uses a quantitative research approach. The subjects of this study were class VIII D MTs Salafiyah Syafiiyah Jombang. The research instruments used were tests and non-tests. The test instruments were pretest and post-test description questions to measure students' mathematical literacy before and after implementing the CORE (Connecting, Organizing, Organizing, Learning) learning model. Reflecting, Extending). While the non-test instruments used were interviews with mathematics teachers in class VIII D to find out the implementation of learning carried out in class. The data analysis technique used was hypothesis testing. However, before testing the hypothesis, the data obtained first First, the normality test and homogeneity test were carried out. Based on the calculation of the paired sample t test, it shows that the t value is 13,818 with a significance of 0,000. The significance value shows 0.000 < error level of 0.05, so it can be concluded that Ha is accepted. Acceptance of this Ha means that there are differences in the level of mathematical literacy of class VIII students of MTs Salafiyah Syafiiyah Jombang before and after implementing the CORE learning model.